In Becoming. The Relationality of Psychedelic Substances - Sadowska, Zuzanna (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2022)
Psychoactive substances are subject to legal control imposed through the system of medical prescription or legal prohibition, with legal penalties for their unauthorized use. Consumption of drugs in non-medical contexts is often labeled as “drug abuse”, and the substances used in this way as “narcotics”, a term connoting illegality (Goodman et al., 2017). While legal, medical, and popular discourses attempt to establish the distinction between “illicit drugs” and “medicines” by creating the presumptive ontologies of drugs, such an approach to psychoactive substances has been criticized by researchers associated with the “ontological turn”. They have discarded the assumption of drugs as fixed, ready-made, singular objects, postulating we think about substance use as a mutable system of relations intertwined in the broader assemblages and ecologies of drug use. In this article, by using ethnographic examples and through the analysis of research conducted within the “psychedelic turn”, I demonstrate the fluidity and multiplicity of psychoactive substances and examine diverse ways through which psychoactive substances are stabilized and destabilized in three different domains – legal drug regulation, psychedelic renaissance discourse, and at the level of the experiences of users.
24 cm
Keywords: etnografia -- czasopisma; drug use and abuse; psychedelic-assisted therapy; psychedelic renaissance; the ontological turn; knowledge production practices; drug scheduling

Where Should the “Ontological Turn” Turn? Methodological Dilemmasi n the Ethnography of Catholic Charismatic Renewal Community - Biernacka, Adrianna (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2018)
Podczas badań przeprowadzonych we wspólnocie Odnowy w Duchu Świętym w Przeworsku, starałam się zrozumieć, jak moi rozmówcy i rozmówczynie rozumieli posługę darem charyzmatycznym. Inspiracją metodologiczną dla moich badań była perspektywa zwrotu ontologicznego (zwłaszcza w rozumieniu Martina Holbraada i Mortena Axela Pedersena). Niniejszy artykuł pokazuje, jak to podejście metodologiczne wpłynęło na moje badania – co pozwoliło mi dostrzec, a co utrudniło. W podsumowaniu staram się przedstawić, w jaki sposób zwrot ontologiczny mógłby się rozwijać, aby przezwyciężyć wcześniej zasygnalizowane problemy
il. ; 24 cm
Keywords: zwrot ontologiczny; Ruch Odnowy w Duchu Świętym; antropologia chrześcijaństwa; dar charyzmatyczny